Mergers and Acquisitions: Navigating HRM challenges for successful integration - S, Bangura,; Chitamba, Anos; Ngidi, Lucia Zothibile (Edelweiss Applied Science and Technology, 2025)
Mergers and acquisitions (M&A) are transformative corporate strategies aimed at enhancing competitive advantage, market share, and operational efficiency. However, the success of M&A ventures often hinges not solely on financial and strategic alignment but also on the effective integration of human resource management (HRM) practices. This paper explores the critical HRM challenges encountered during M&A processes, including cultural integration, talent retention, post-M&A rewards and integration, uncertainty leading to turnover, and communication management. Drawing on and employing an integrative review to examine current theories related to mergers and acquisitions (M&A) as well as pertinent human resource management that contribute to successful mergers. A comprehensive review of both secondary and primary data sources, including articles, publications, and other relevant documents, was conducted using various research methodologies. Findings revealed strategies to mitigate these challenges, such as fostering employee engagement, regular updates from management regarding the M&A process, and considerations for retaining top talent and addressing compensation issues. Additionally, enhancing employee well-being and leveraging digitalization are considered critical factors in overcoming the challenges linked to M&A from an HRM perspective. By emphasizing the human element, this study underscores how a well-orchestrated HRM strategy can drive successful integration regarding M&A.